Equivalent retention of gains at 1 year after training with constraint-induced or bimanual therapy in children with unilateral cerebral palsy - Sakzewski, L.; Ziviani, J.; Abbott, D.; MacDonell, R.; Jackson, G.; Boyd, Roslyn (2011)
Objectives. To determine retention of treatment outcomes at 52 weeks following a matched-pairs randomized comparison trial of constraint-induced movement therapy (CIMT) and bimanual training (BIM). Methods. Sixty-four children (mean age = 10.2 ± 2.7 years, 52% male) were included. The Melbourne Assessment of Unilateral Upper Limb Function (MUUL), Assisting Hand Assessment (AHA), and Canadian Occupational Performance Measure (COPM) were the primary outcome measures. Evaluations were at baseline and at 26 and 52 weeks. Results. There were no baseline differences between groups on any measure. No significant differences were found between groups on primary outcomes at 52 weeks. Both groups retained the significant gains made from baseline to 26 weeks at the 1-year follow-up assessment for unimanual capacity on the MUUL, for bimanual performance on the AHA, and on the COPM. Conclusion. Intensive unimanual and bimanual training can both lead to long-term significant improvements in unimanual capacity, bimanual performance, and individualized outcomes. Gains established at 26 weeks were maintained at 12 months postintervention despite most children receiving no direct therapy during that time. © 2011 The Author(s).